The Implementation of Indonesian National Standard (SNI) on Palm Oil Seed Production in Indonesia - Isharyadi, Febrian; Ayuningtyas, Utari; Kristiningrum, Ellia; Prasetya, Bambang; Dulbert Tampubolon, Biatna; Tjahyo Eka Darmayanti, Nur; Budi Mulyono, Ary; Restu Wahono, Daryono; Aliyah, Novin; Dwi Susmiarni, Rika; Wulansari, Nuri (Jurnal Penelitian Kelapa Sawit, 2024)
The use of superior oil palm seeds is one of the factors that determine the productivity and fruit quality produced by oil palm plantation. To obtain quality oil palm seeds, quality control is also needed in the oil palm seed production process. Standar Nasional Indonesia (SNI) number 8211:2015 concerning oil palm seeds is a standard that contains quality parameters that must be met in every oil palm seed production process. However, information regarding the implementation of SNI 8211:2015 at the time of oil palm seed production is unknown. This study aims to identify the implementation of SNI 8211:2015 in each process of oil palm seed production, so that this will be an overview and facts related to quality assurance carried out by producers in producing quality oil palm seeds. This study uses a quantitative descriptive method by conducting a survey of oil palm seed producers as respondents regarding the implementation of benchmarks on SNI 8211:2015. The results showed that of the 13 respondents who produced oil palm seeds, the implementation of SNI 8211:2015 in the production process had been carried out well in 4 (four) main stages, there are breeding, seed reproduction, seed processing, and packaging. This shows that the quality of the oil palm seeds produced is guaranteed. Further investigations need to be carried out on other critical points that have the potential to cause illegal seeds to circulate in Indonesia, so that the productivity of oil palm plants in Indonesia can be increased by using superior oil palm seeds.